2011
DOI: 10.1111/j.1755-0998.2011.03068.x
|View full text |Cite
|
Sign up to set email alerts
|

Permanent Genetic Resources added to Molecular Ecology Resources Database 1 June 2011–31 July 2011

Abstract: This article documents the addition of 112 microsatellite marker loci and 24 pairs of single nucleotide polymorphism (SNP) sequencing primers to the Molecular Ecology Resources Database. Loci were developed for the following species: Agelaius phoeniceus, Austrolittorina cincta, Circus cyaneus, Circus macrourus, Circus pygargus, Cryptocoryne • purpurea Ridl. nothovar. purpurea, Mya arenaria, Patagioenas squamosa, Prochilodus mariae, Scylla serrata and Scytalopus speluncae. These loci were cross-tested on the fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…We sequenced 595 bp of the mitochondrial DNA control region (CR) from each sample. The sequenced region is highly variable and information dense (Barker et al 2011), and thus serves as an excellent marker for differentiation of recently diverged populations. For most samples, CR was amplified and sequenced in one fragment, using primers BBCR_For1 (5′-CCCCCAGTACATTTTCTTCTT-3′) and BBCR_Rev1 (5′-CCAAGTGTAGGAGGTCGGTAT-3′).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We sequenced 595 bp of the mitochondrial DNA control region (CR) from each sample. The sequenced region is highly variable and information dense (Barker et al 2011), and thus serves as an excellent marker for differentiation of recently diverged populations. For most samples, CR was amplified and sequenced in one fragment, using primers BBCR_For1 (5′-CCCCCAGTACATTTTCTTCTT-3′) and BBCR_Rev1 (5′-CCAAGTGTAGGAGGTCGGTAT-3′).…”
Section: Methodsmentioning
confidence: 99%
“…We genotyped each individual at five short tandem repeat (STR or microsatellite) loci (Ap49, Ap64, Ap115, Ap146, and Ap160) developed specifically for A. phoeniceus , which were previously tested for optimal annealing, consistent amplification, homology, and variability in both bicolored and typical populations (Barker et al 2011). These loci were selected because they yielded the smallest expected products, a critical factor in PCR amplification from degraded material (Schneider et al 2004).…”
Section: Methodsmentioning
confidence: 99%
“…The detailed descriptions of methods used (1) for extracting DNA of larval and post-larval recruits, (2) for genetically identifying veligers as true M. arenaria individuals using a single nested multiplex polymerase chain reaction assay (Larsen et al 2005), and (3) for genotyping individuals at seven microsatellite loci (Mar1, Mar3, Mar4, Mar5, Mar6, Mar7 and Mar8) (Barker et al 2011) are all provided in Online Resource 4. In summary, DNA was extracted from 386 larval and post-larval recruits (see n E in Table 1).…”
Section: Sample Characteristicsmentioning
confidence: 99%
“…Up until now, these kinds of studies were scarce, mostly due to difficulties associated with developing polymorphic genetic markers, especially for bivalves, and with extracting DNA from single microscopic larvae. But recent technological advances have now rendered this kind of approach much more feasible (Larsen et al 2005;Zhan et al 2008;Barker et al 2011).…”
Section: Introductionmentioning
confidence: 98%
“…However, the microsatellite loci available for molluscs species are still limited [4] and until now, studies of genetic variation on M. arenaria were conducted using only allozymes [5] and COI sequences [6]. Recently, 8 microsatellite loci for this species have been described [7]. Computer simulations showed that over 30 microsatellite loci should be used when inferring aspects of the evolutionary history of populations, [8] therefore, additional microsatellite loci are needed for population genetic studies.…”
Section: Introductionmentioning
confidence: 99%